An Optimum Imaging Scheme for IVUS Arrays: Eccentric Cylinder Wave Compounding. (May 2019) - Li, Mingxia; Feng, Zhihua
With the development of integrated circuit (IC) technologies, complex transmitting and receiving circuits can be integrated into miniature intravascular ultrasound (IVUS) catheters, making it possible to adopt better synthesizing schemes for better imaging. Eccentric cylinder wave compounding should be an optimum synthesizing scheme for the small size cylinder shaped catheter. Eccentric cylinder waves centered at different points are emitted, signals are collected after each emission, and images can be synthesized with easy post processing. Detailed analyses about resolution and grating lobes were made; the optimum eccentric distance was determined. Simulations were done to examine the resolution, signal-to-noise ratio, and resistance to crosstalk and nonuniformity of arrays. Dual apodization and magnitude-based deconvolution were applied to further improve the results.